A Clinical Audit Of Management Of Third And Fourth Degree Perineal Tears - Saida Abrar; Raheela Mohsin Rizvi; Urooj Kashif; Admin (Journal of the Pakistan Medical Association, 2021)
Objective: To perform a clinical audit of the practices of third and fourth degree preineal tears management in our institution. Methods: A review of medical records was performed, of women having singleton term vaginal delivery sustaining obstetric anal sphincter injuries (OASIS) at Aga Khan University Hospital (AKUH), Karachi from January 2008 to December 2018. We compared the change in practices regarding management of OASIS with the results of our previous study done at AKUH in 2008. Results: The frequency of OASIS in our department is 0.56% (142/25370). The documentation of OASIS improved compared to previous study ( 20.7% to 87%). There was also a significant increase in documentation of the method of repair, use of delayed absorbable suture material for the repair of external anal sphincter and follow-up at 06 weeks to see the success of repair and plan next delivery. The use of vaccum vaginal delivery increased to 27(19%) from 5(4%) but there was decrease in the OASIS complicated by instrumental vaginal deliveries, which may be due to the decrease in the use of forceps from 64% to 26%. Conclusions: Despite of increase in the number of deliveries , frequency of OASIS remained similar to the previous study. There was a significant increase in the vaccum vaginal delivery, documentation of degree of tears, use of delayed absorbable suture material and long-term follow-up and decrease in the use of forceps. The compliance to international guideline increased as compared to our previous paper. Continuous...